PENGARUH AUDIT INTERNAL TERHADAP MITIGASI RISIKO OPERASIONAL PERBANKAN SYARIAH - Erika Amelia; Muhammad Harfi Ramdan (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2019)
Internal audit as a supervisor in banking should have a very important role in operational risk, but in banks that already have internal audit institutions in it are still experiencing operational risk, so this study aims to analyze and determine the effect of internal audit on operational risk mitigation in Islamic banking and the main factors of internal audit that affect the operational risk of sharia banking. The variable that is the focus of this research is internal audit (X) as a free variable and banking operational risk (Y) as the dependent variable. Data obtained through questionnaires, this study uses a simple linear regression test to determine the effect of these two variables and test the coefficient of determination to determine the magnitude of the effect of variable (X) on (Y) and calculation of maximum values to determine the main factors of internal audit that affect operational risk banking. the results of data processing are done using Ms. Excel 2007 and the SPSS 17.0 application. The results in the study concluded that internal audits affect the operational risk of Islamic banking. The magnitude of the effect is 52.4% while the rest is influenced by other factors. The most influential main factor is periodic internal audit reporting to the Board of Commissioners regarding compliance with policies and procedures, internal audits evaluating risk management measures to ensure accuracy of risk exposures (vulnerable objects) and internal audits evaluating the reliability of information produced by computer system and accounting system.Keywords: audit, internal audit, banking risk, linear regression, determination coefficient